DIRETRIZES PARA GESTÃO DE CARREIRA DE JOVENS LÍDERES: O CASO DA INDÚSTRIA METALMECÂNICA NO SUL FLUMINENSE - Farias, Cristiana Ferreira de (2015)
This dissertation studies the career management process in industrial organizations focused on the young leaders. This study analyzes the organizational context and the current tendency of companies to accelerate the career of young professionals, leading them to the strategic management positions. Publications about Career Management are integrated into the subject of people management and the main Human Resources processes. This dissertation is intended to raise guidelines to be considered in structuring programs of career management of young leaders. The conclusions obtained include set of guidelines to be considered by the organization to attract, motivate and engage, as well as to develop and retain talents.